Manfaat Penerapan ERP Berbasis SAP bagi End-User di PT.XY - Ira Yanti; Isti Rahayau (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study provides an in-depth analysis of the benefits of implementing a SAP-based Enterprise Resource Planning (ERP) system for end-users at PT XY, an Indonesian airport management company. A qualitative case study approach was applied through comprehensive in-depth interviews and direct observations of accounting division staff who actively utilize the SAP Financial Accounting (FI), Controlling (CO), and Materials Management (MM) modules as part of their daily operations. The findings demonstrate that SAP implementation significantly enhances work efficiency, data accuracy, and overall operational productivity across multiple business processes. The system facilitates seamless cross-departmental integration, reduces manual errors, accelerates financial reporting, and supports real-time, data-driven decision-making. Furthermore, SAP strengthens internal coordination by providing consistent, centralized, and easily accessible information to all relevant stakeholders. Key challenges identified include limited network access, server congestion during peak hours, and difficulties with remote connections when accessing the system outside the office environment. The company addressed these issues through regular user training, provision of secure Virtual Private Network (VPN) access, expansion of server capacity, and a strategic plan to migrate to cloud-based SAP S/4HANA to improve flexibility, scalability, and long-term system reliability. The findings not only enrich the literature on ERP adoption, with practical guidance for other organizations seeking to plan, implement, and evaluate ERP systems to meet their own business needs, including effective human resource planning and change management strategies.